Review of Bacterial Nanocellulose as Suitable Substrate for Conformable and Flexible Organic Light-Emitting Diodes - Faraco, Thales Alves; Fontes, Marina de Lima; Paschoalin, Rafaella Takehara; Claro, Amanda Maria; Gonçalves, Isabella Salgado; Cavicchioli, Mauricio; Farias, Renan Lira de; Cremona, Marco; Ribeiro, Sidney José Lima [UNESP]; Barud, Hernane da Silva; Legnani, Cristiano (MDPI, 2023)
As the development of nanotechnology progresses, organic electronics have gained momentum in recent years, and the production and rapid development of electronic devices based on organic semiconductors, such as organic light-emitting diodes (OLEDs), organic photovoltaic cells (OPVs), and organic field effect transistors (OFETs), among others, have excelled. Their uses extend to the fabrication of intelligent screens for televisions and portable devices, due to their flexibility and versatility. Lately, great efforts have been reported in the literature to use them in the biomedical field, such as in photodynamic therapy. In tandem, there has been considerable interest in the design of advanced materials originating from natural sources. Bacterial nanocellulose (BNC) is a natural polymer synthesized by many microorganisms, notably by non-pathogenic strains of Komagataeibacter (K. xylinus, K. hansenii, and K. rhaeticus). BNC shows distinct physical and mechanical properties, including its insolubility, rapid biodegradability, tensile strength, elasticity, durability, and nontoxic and nonallergenic features, which make BNC ideal for many areas, including active and intelligent food packaging, sensors, water remediation, drug delivery, wound healing, and as conformable/flexible substrates for application in organic electronics. Here, we review BNC production methods, properties, and applications, focusing on electronic devices, especially OLEDs and flexible OLEDs (FOLEDs). Furthermore, we discuss the future progress of BNC-based flexible substrate nanocomposites.
Keywords: bacterial nanocellulose; BNC; FOLED; OLED